Analisis Pencemaran Logam Berat Timbal (Pb) dan Zinc (Zn) di Perairan PPS Kendari - Subarkah, Mulud; Srikandi, Eka Dian; Adami, Aryani; Sumarlin, Sumarlin (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2021)
The maintenance of fishing vessels at Perikanan Samudera Kendari Harbor (PPS) is often carried out by fishing vessels maintenance ventures such as painting, cutting, annihilating, welding, spraying by using sand, changing oils, repairing machines, and other maintenance duties. This industry could potentially lead to degradation of environmental quality, one of which is heavy metal contamination. Therefore, the purpose of this study is to know the degree of heavy metal contamination at PPS Kendari, based on physics parameters (water brightness) and chemical parameters (Pb and Zn). Lead content (Pb) at the first station (1), the second station (2) and the third station (3) was undetected. Meanwhile, zinc content (Zn) at the first station (1) and the second station (2) was also undetected. At the third station (3), the zinc content was detected of 0.006 mg/L. This value is still under standard quality, namely of 0.1 mg/L. Zn contamination index was 0.053. This value is still within 0 ≤ Pij ≤ 1,0 range which meant the content of Zn at PPS Kendari still meets the standard quality (good condition).